USULAN PENGEMBANGAN EKOWISATA JAYAGIRI BERBASIS MASYARAKAT LOKAL - Yopy Maulana (Jurnal Hospitality dan Pariwisata, 2017)
Planning the development of tourism is very important because today and in the futurewill continue to shift travel market. Motives, interests, tastes, demands, and behavior oftravelers is constantly changing in this regard needs to be responded to appropriately.Moreover, the availability of a quality product to wane. With such changes innovativeproducts that are not obviously will not be sold in the market. Moreover, competitiveproducts and services in the travel market tends to increase with the degree of quality ismuch better. Therefore, the planning into action absolutely necessary. Good planningmeans will produce a strategy to increase competitiveness (competitiveness) productsand profits at the company level or travel perpetrator. In the plan should be reflected inthe terms must be met and what functions need to be carried out by the perpetrators.Explained that there are five main pillars that support the building eco-tourismdevelopment plan namely:a. Sustainable tourism developmentb. Political and administrative structure that includes local government tourismc. Legislationd. Regional autonomye. The diversity of the tourism potentialThe construction of this area is to assist the government of West Java in an activerole in the tourism industry in general, by utilizing existing resources optimally. Thisarea was built with the intention to take an active role in solving the constraints ofdevelopment and the potential problems that exist so far in the area of Subang RegencyJayagiri and in general by:a. Utilizing optimum use of natural and human resources so as to provide greater addedvalue and increase productivity.b. Helping local governments to help increase the number of tourists that will generateincome and empower the local community in terms of management and development.Keywords: tourists. Competitiveness, sustainable tourism, Jayagiri, human resources.